Effects of design parameters on thermal parameters for an adaptive cycle turbofan - Aygun, Hakan; Ekmekci, Ismail; Turan, Onder (Springer, 2023)
In this study, effects of high-pressure compressor pressure ratio (HPC PR) and bypass ratio (BPR) regarding adaptive cycle turbofan (ACT) engine on performance parameters and second law parameters of thermodynamics involving Carnot, Curzon-Ahlborn, Caputo, thermal and exergy efficiencies are dealt with. For this aim, HPC PR changes between 4 and 6, and bypass ratio ranges between 0.3 and 0.6. At same altitude of 10,000 m, comparative analysis is performed for efficiency behavior of ACT engine at military mode (MM) and afterburner mode (ABM). Better understanding of performance improvements of a military aircraft can be possible by investigating these efficencies for different design variables. Based on these computations, environmental and irreversibility parameters involving specific irreversibility production and environmental effect factor regarding ACT engine are dealt with at both modes. According to performance outcomes, SFC of the ACT engine decreases by 7.66% at MM, whereas it increases by 0.34% at ABM due to higher BPR. Moreover, it diminishes by 4.98% at MM and decreases by 0.42% at ABM with influence of the elevated HPC PR. As for efficiency analyses, exergy efficiency of ACT engine increases from 20.04 to 21.7% at MM, whereas it decreases 17.43 to 17.37% at ABM with effect of raised BPR. The higher HPC PR leads to increase from 20.32 to 21.38% at MM and from 17.39 to 17.46% at ABM. Among the components, the combustor has the lowest exergy efficiency, which is favorably affected from both variables at MM. Finally, environmental effect factor of the ACT becomes lower thanks to the higher BPR and HPC PR at MM. However, at ABM, to increase these variables do not result in lower EEF. Therefore, considering design parameters according to operation modes could lead in finding more meaningful outcomes. It is thought that this study helps in analyzing of thermodynamic parameters with respect to different design parameters.
Keywords: Energy; Caputo efficiency; Adaptive cycle turbofan; Design variables; Curzon-Ahlborn efficiency